2019
DOI: 10.3892/ijmm.2019.4150
|View full text |Cite|
|
Sign up to set email alerts
|

Human peripheral blood‑derived exosomes for microRNA delivery

Abstract: Exosomes serve important functions in cell-to-cell communication and biological functions by serving as a delivery cargo shuttle for various molecules. The application of an improved delivery method for microRNAs (miRNAs/miRs) may enhance their potential as a therapeutic tool in cardiac diseases. Thus, the present study investigated whether human peripheral blood-derived exosomes may be used as a delivery cargo system for miRNAs, and whether the delivery of miR-21 using a human peripheral blood derived-exosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 46 publications
0
24
0
1
Order By: Relevance
“…Furthermore, miR-21 mimic-loaded exosomes enhanced fibrosis in the mouse model of myocardial infarction. 52 Similarly, a study of renal fibrosis reported that treatment with miR-21 significantly aggravated the TGF-β-induced epithelial fibroblast phenotype. 53 Thus, overexpression of mir-21 may tend to fibrosis.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, miR-21 mimic-loaded exosomes enhanced fibrosis in the mouse model of myocardial infarction. 52 Similarly, a study of renal fibrosis reported that treatment with miR-21 significantly aggravated the TGF-β-induced epithelial fibroblast phenotype. 53 Thus, overexpression of mir-21 may tend to fibrosis.…”
Section: Discussionmentioning
confidence: 97%
“…Several EV formulations have been enriched using transfection agents or membranepermeabilizing strategies and evaluated in the context of cardiovascular applications to decrease cardiac fibrosis, modulate the inflammatory response and to increase angiogenesis (Table 1). For example, miRNA-21-5p has a critical role in the development of fibrosis after MI, regulating several gene targets including SMAD family member 7 (Smad7), sprout RTK signalling antagonist 1 and phosphatase and tensin homolog (PTEN) 141 . Human peripheral blood-derived EVs enriched for miR-21 inhibitors reduced fibrosis in a mouse model of MI as compared to non-modified EVs.…”
Section: 22-post-isolation Methodsmentioning
confidence: 99%
“…Over the last decade, miRNAs have emerged as key regulators of several cellular processes, including angiogenesis, and certain miRNAs, such as miR-132, miR-126, miR-451a, miR-494-3p, miR-16a-5p and miR-23a-3p, have been shown to play key roles in the vasculature in both endothelial and perivascular cells ( 11 , 12 ). In addition, previous studies have demonstrated that EXs contain a large number of miRNAs, and EXs may deliver these miRNAs to their target cells ( 13 - 15 ). It was previously reported that DC infiltration is significantly increased in the infarcted myocardium and plays an important role in angiogenesis and cardiac healing after MI ( 6 ).…”
Section: Introductionmentioning
confidence: 99%